Invigoration of various sized sunflower seeds: an evaluation of germination and seedling quality parameters under different aging conditions: INVIGORATION OF SUNFLOWER SEEDS FOR QUALITY MAINTENANCE DURING AGING - RUPA DAS; SAIKAT BISWAS (Journal of Oilseeds Research, 2021)
An experiment was conducted at laboratory of Department of Seed Science and Technology, Institute of Agricultural Science, University ofCalcutta, West Bengal, India to evaluate the response of various sized sunflower seeds (large, medium, small, composite) to invigoration treatments (control, red chilli powder@ 1g/kg of seed, bleaching powder@ 2 g/kg ofseed, aspirin@ 50 mg/kg ofseed) under various aging conditions. Results showed that compared to aged seeds, germination and seedling quality parameters of sunflower were best under fresh seeds. Among aging conditions, naturally aged seeds showed less quality deterioration than seeds under accelerated aging. Irrespective of aging and no aging, large sized seeds treated with either red chilli powder or bleaching powder showed good seedling quality. Specifically, freshly harvested large seeds produced vigorous seedling when treated with red chilli powder (vigour index-I: 1833.88, vigour index-II: 2174.52) or bleaching powder (vigour index-I: 1808.76, vigour index-II: 2200.09). Among two aging conditions, seed quality deterioration was better checked and repairing of damage to an extent was done over control when large seeds were treated with powders specially, red chilli powder (vigour index-I: 1079.61, vigour index-II: 1128.59) or bleaching powder (vigour index-I: 1060.07, vigour index-II: 1053.21) under natural aging condition.